Keep me posted [large type] - Beazley, Lisa (Center Point Large Print, 2016)
Life veered in sharply different directions for the once-close Sunday sisters. Beautiful and bighearted Sid lives an expat's life of leisure in far-off Singapore, while harried, iPhone-clutching Cassie can't seem to make it work as a wife and mom to twin toddlers in Manhattan. It doesn't help that Sid spurns all social media while Cassie is addicted to Facebook. So when Sid issues a challenge to reconnect the old-fashioned way-- through real, handwritten letters-- Cassie figures, why not? The letters become a kind of mutual confessional... until one of Cassie's infamous lapses in judgment comes back to bite her, and all of the letters wind up the one place you'd never, ever want to see them: the Internet.